Answer:
The solution of the Given matrix
( x₁ , x ₂ ) = ( - 5 , 4 )
Explanation:
Step(i):-
Given equations are x₁+4 x₂ = 11 ...(i)
2 x₁ + 7 x₂= 18 ...(ii)
The matrix form
A X = B
![\left[\begin{array}{ccc}1&4\\2&7\\\end{array}\right] \left[\begin{array}{ccc}x\\y\\\end{array}\right] = \left[\begin{array}{ccc}11\\8\\\end{array}\right]](https://img.qammunity.org/2021/formulas/mathematics/college/olc0fxzrz421z07x47vp86l2pmdxmtqevq.png)
Step(ii):-
![\left[\begin{array}{ccc}1&4\\2&7\\\end{array}\right] \left[\begin{array}{ccc}x\\y\\\end{array}\right] = \left[\begin{array}{ccc}11\\8\\\end{array}\right]](https://img.qammunity.org/2021/formulas/mathematics/college/olc0fxzrz421z07x47vp86l2pmdxmtqevq.png)
The Augmented Matrix form is
![[AB] = \left[\begin{array}{ccc}1&4&11\\2&7&18\\\end{array}\right]](https://img.qammunity.org/2021/formulas/mathematics/college/q9kkp7gj2bsqqfd71ulp93a60zvwx0roj8.png)
Apply Row operations, R₂ → R₂-2 R₁
The matrix form
![\left[\begin{array}{ccc}1&4\\0&-1\\\end{array}\right] \left[\begin{array}{ccc}x\\y\\\end{array}\right] = \left[\begin{array}{ccc}11\\-4\\\end{array}\right]](https://img.qammunity.org/2021/formulas/mathematics/college/njh2mwmy58japfhbtye2mi5zirxmehnf1q.png)
The equations are
x₁ + 4 x₂ = 11 ...(a)
- x ₂ = - 4
x ₂ = 4
Substitute x ₂ = 4 in equation (a)
x₁ + 4 x₂ = 11
x₁ = 11 - 16
x₁ = -5
Final answer:-
The solution of the Given matrix
( x₁ , x ₂ ) = ( - 5 , 4 )